POLITICIZED NARRATIVE THERAPY: A Reckoning and a Call to Action - Dumaresque, Renee; Thornton, Taylor; Glaser, Daniela; Lawrence, Anthony (Canadian Social Work Review / Revue canadienne de service social, 2018)
Using a poly-vocal approach, this piece calls for the interruption and interrogation of narrative therapy’s colonial associations (White & Epston, 1990), and the cooption of narrative therapy by psychiatry under the guise of progressiveness (J. Poole, Personal Communication, January 31, 2017). We locate narrative therapy in the neoliberal geography of recovery and marketization, where social problems are coded as individual struggles, personal stories are used as mental health marketing material, and the burden of wellness enables psychiatric governance (Costa et al., 2012; Morrow, 2013; Poole, 2011). Drawing on Sefa Dei and Asgharzadeh’s (2001) anti-colonial discursive framework, critical race theory and its technique of counter-storytelling, Patricia Hill Collins’ (1990) Black feminist thought, and anti-sanist theorizing, we explore the possibility of reimagining narrative therapy for political ends. Throughout this piece, we draw on narrative techniques to move beyond an individual understanding of distress, connecting personal struggles to the broader social and political context. We do this by extending a political lens to the four steps taken in a mainstream narrative approach. We have chosen to use case studies informed by our own lived experiences in order to highlight the potential that we see in narrative work. This approach does not leave narrative therapy unchallenged and we understand that by remaining in a narrative framework housed in social work practice we cannot truly separate our approach from colonial care (Baskin, 2016; Lee & Ferrer, 2014). Rather, we hope to start a critical and transparent conversation that begins to explore the reconceptualization of narrative therapy for the purpose of deconstructing dominant discourses and making any colonial connections visible.